EСТЕТСКА (РЕ)КОНСТРУКЦИЈА НА ЕДНА ТРАУМА (Journal of Contemporary Philology, 2018)
The man is in constant relation to the reality surrounding him and based onhis actions, opinions and decisions he creates his own I, which is inevitablyconditioned by the relationship of himself – andthe Other, in order to surpassthe unbridgeable gap, which forever separates him and makes him closed. Examples which show in their story how to incorporate the relation person– reality – identity, but which also incorporate problems of building identity,at the same time as deeply immersed trauma, the relation towards others and,in the end, the procedure for breaking (disintegrating) the projected reality andundermining the basis on which it was built on – previously accepted values of the Good, Beautiful – are the films Persona (Ingmar Bergman, 1966), Eyeswide shut (Stanley Kubrick, 1999), Mulholland Drive (David Lynch, 2001) and Irreversible (Gaspard Noé, 2002). Trauma, which penetrates into each of these film narratives is a starting impulse of metamorphosing (doubling), that recreates the world that is imposedin front of the viewers.
Keywords: траума; подвоеност; персона; идеално-јас; идентитет